2011
DOI: 10.1007/s00436-011-2334-3
|View full text |Cite
|
Sign up to set email alerts
|

Failure of combination therapy with imidocarb dipropionate and toltrazuril to clear Hepatozoon canis infection in dogs

Abstract: Current treatments with imidocarb dipropionate for infected dogs with Hepatozoon canis do not always provide parasitological cure. The objective of this study is to determine whether concomitant use of toltrazuril may potentiate the effect of imidocarb dipropionate in the management of H. canis infection (HCI). Twelve dogs were determined to have naturally HCI based on clinical signs, identification of the parasite in blood smears, and serologic assay. The animals were allocated randomly to one of two groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Many dogs have concurrent infections with vector-borne agents such as E. canis and Babesia spp., and deciding each agent’s contribution to signs is difficult. Various treatments have been used but none are fully effective [34]. …”
Section: Resultsmentioning
confidence: 99%
“…Many dogs have concurrent infections with vector-borne agents such as E. canis and Babesia spp., and deciding each agent’s contribution to signs is difficult. Various treatments have been used but none are fully effective [34]. …”
Section: Resultsmentioning
confidence: 99%
“…Imidocarb dipropionate (5-6 mg/kg every 14 days) is used to treat canine hepatozoonosis (Baneth and Weigler, 1997), but the therapeutic efficacy is inconsistent and will not necessarily result in a parasitological cure (Ogunkoya et al, 1981;Sasanelli et al, 2010;De Tommasi et al, 2014). Similarly, the efficacy of toltrazuril is inconsistent (Krampitz and Haberkorn, 1988;Macintire et al, 1997;Tort et al, 2007) and results from studies on combination therapies with emodepside/toltrazuril (Procox® suspension for dogs (Altreuther et al, 2011)) and clindamycin (De Tommasi et al, 2014), and imidocarb dipropionate/toltrazuril (Pasa et al, 2011) showed no statistically significant difference in clinical efficacy compared with monotherapies. However, Pasa et al (2011) reported a better overall clinical response with imidocarb dipropionate/toltrazuril compared with imidocarb dipropionate treatment alone (Pasa et al, 2011).…”
Section: Canine Hepatozoonosis Is a Well Characterised Disease With Fmentioning
confidence: 99%
“…The drug of choice has long been ID, although the treatment results from this drug have been inconsistent (PASA et al, 2011).…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, Pasa et al (2011) tried to improve the efficacy of H. canis treatment with an association of ID (at a dose of 6 mg.kg -1 subcutaneously twice, 14 days apart) with oral toltrazuril (at 10 mg.kg -1 once daily for the first five treatment days). The overall clinical efficacy of ID with and without toltrazuril was 83.3% and 66.7%, respectively, and the authors concluded that toltrazuril did not produce any additional benefit for ID therapy.…”
Section: Treatmentmentioning
confidence: 99%